Transformation of students towards quality workforce in achieving Vision 2020 / Ibrahim Abu Shah and Iris Syawe Seh Ling - Abu Shah, Ibrahim; Seh Ling, Iris Syawe (1992)
Malaysia desires to achieve the goal of becoming a fully developed nation by the year 2020. In order to fulfil this aim, the Malaysian economy is targeted to grow at 7% per annum during the time frame of the Second Outline Perspective Plan 1991-2000. With this transformation, Malaysia is entering an era of rapid industrialization. Thus, there is a demand for high-level technical skills, management and entrepreneurial capabilities as well as increased technological development and improved capital utilization. However, one of the problems which need to be resolved is the current lack of trained and skilled manpower. According to the Second Outline Perspective Plan, human resource development will assume new importance. Competitiveness, productivity, innovativeness and capability in management of new technologies in Malaysia will be determined by the quality of her human resources. A productive and skilled labour force must be developed with strong ethical and moral values and a commitment to excellence. Sarawak, the biggest state in Malaysia should be able to contribute towards human resource development but the educational level of the labour force particularly the indigenous labour force lags behind the educational level of the labour force for the nation as a whole and the illiteracy rate of the state is high especially in the vast rural areas. Hence, as steps are being taken under the Sixth Malaysia Plan to enhance the economic well-being of the nation, Sarawak in particular has to increase the amount of education of the labour force. According to the World Development Report 1991, the increase of the average amount of education by one year for a developing country will raise the GDP by 9%. At the lower level, the increase is even more startling, for instance, for those workforce who are illiterate, three years of education will raise the GDP by 27% but the returns to an additional year of school will diminish to about 4% a year for the next three years.